The relationship between environmental factors and magnetic susceptibility in the Ili loess, Tianshan Mountains, Central Asia. (27th March 2018) - Zeng, Mengxiu; Song, Yougui; Li, Yue; Fu, Chaofeng; Qiang, Xiaoke; Chang, Hong; Zhu, Lidong; Zhang, Zhiping; Cheng, Liangqing
Abstract : The mechanisms of the magnetic susceptibility (MS) enhancement of loess from Arid Central Asia (ACA) have received much attention recently. Consensus varies about factors controlling the magnetic properties as well as the environmental implications, and much effort needs to be gone into how surface processes affect the MS. In this study, we collected 214 topsoil, near‐surface loess, and fluvial sediment samples covering different elevations, climatic conditions, and vegetation from the Ili Valley in eastern ACA and analysed their magnetic properties and composition to investigate the factors influencing MS. Redundancy analysis (RDA) was employed to assess the relationship between environmental indicators and environmental factors. Our results show that (a) the concentration of pedogenic magnetic particles in the Ili loess and topsoils is limited. χlf is higher in loess but lower in paleosol, mainly attributable to changes in wind intensity; (b) the mean χfd, χfd %, and χlf values of topsoil are lower in the desert steppe and forest–meadow zones, but highest in the montane steppe zone, and are not positively associated with vegetation coverage and the intensity of pedogenic processes; and (c) elevation exerts the most important impact on topsoil χfd and χfd %, while χlf is influenced more by temperature than precipitation. (d) The magnetic enhancement could be mainly attributed to wind velocity; we also should consider elevation and other factors such as local material, climatic conditions, and distance to the dust source when interpreting the paleoclimatic or paleoenvironmental significance of magnetic parameters.